2016
DOI: 10.1371/journal.pntd.0004435
|View full text |Cite
|
Sign up to set email alerts
|

A Proteomic Approach Identifies Candidate Early Biomarkers to Predict Severe Dengue in Children

Abstract: BackgroundSevere dengue with severe plasma leakage (SD-SPL) is the most frequent of dengue severe form. Plasma biomarkers for early predictive diagnosis of SD-SPL are required in the primary clinics for the prevention of dengue death.MethodologyAmong 63 confirmed dengue pediatric patients recruited, hospital based longitudinal study detected six SD-SPL and ten dengue with warning sign (DWS). To identify the specific proteins increased or decreased in the SD-SPL plasma obtained 6–48 hours before the shock compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 29 publications
0
21
0
Order By: Relevance
“…Receiver operating characteristics (ROC) and the area under the curve (AUC) were used to evaluate the predictive value of protein biomarkers for GDM. An AUC value between 0.5 to 0.75 was considered to have predictive value, and the value ≧0.75 was considered to be a good diagnostic index [13]. p-value <0.05 was considered to be significant difference.…”
Section: Resultsmentioning
confidence: 99%
“…Receiver operating characteristics (ROC) and the area under the curve (AUC) were used to evaluate the predictive value of protein biomarkers for GDM. An AUC value between 0.5 to 0.75 was considered to have predictive value, and the value ≧0.75 was considered to be a good diagnostic index [13]. p-value <0.05 was considered to be significant difference.…”
Section: Resultsmentioning
confidence: 99%
“…The question of the existence of biological markers of severe dengue as prognostic signatures of the risk of evolution of disease was addressed [18,19]. Nhi et al identified plasma proteins exhibiting different relative concentrations in patients diagnosed for a severe dengue [20]. Nikolayeva et al worked on a small number of gene expression markers to detect severe cases of dengue fever from blood samples from young patients with secondary infection [21].…”
Section: Asymptomatic and Symptomatic Cases Of Denguementioning
confidence: 99%
“…In terms of viral infections, Dengue fever, Hepatitis B and C, HIV and Simian immunodeficiency virus (SIV) have been studied using iTRAQ of plasma and serum samples. Liu et al compared plasma from individuals with chronic hepatitis B virus‐associated hepatocellular carcinoma (HCC), non‐malignant cirrhosis, chronic hepatitis B, and healthy individuals.…”
Section: Applications Of Isobaric Labeling For Serum and Plasma Protementioning
confidence: 99%
“…172,173 In their study of sepsis in rats, Jiao et al correlated several biomarkers with diagnosis and others with prognosis. 174 In terms of viral infections, Dengue fever, 64,175 Willebrand factor was a potential marker of HCC progression and viral infection. 60…”
Section: Infectionmentioning
confidence: 99%